Understanding the transformation of knowledge-building during online lessons: An analysis of online teaching material related to Grade 12 Financial Mathematics using Legitimation Code Theory - Naidoo, Anashree (University of the Witwatersrand, Johannesburg, 2024)
Education institutions in South Africa and around the world had to close their doors during the lock down in response to Covid-19. As a result of this, many educational institutions proactively engaged in remote teaching to promote a culture of teaching and learning even though learners were not in a physical classroom space. This study aims to comprehend the formation and variation of cumulative knowledge that may occur during distance teaching. To accomplish this, a series of online lessons on the topic of annuities is analysed focusing exclusively on semantic density dimension of Legitimation Code Theory (LCT). LCT is a sociological framework developed by professors Karl Maton and Susan Hood. It aims to understand and analyse the ways in which knowledge is legitimized within different social fields, such as education. Semantic Density within LCT refers to one of the key dimensions used to analyse knowledge practices. It focuses on the degree of complexity and abstractness in the language and symbols used to convey knowledge within a particular field. The online teacher (presenter) focuses on annuities in financial mathematics through six lessons where the knowledge is revised and applied in different contexts. This study focused on the analysis of the online lesson transcripts, using a translation device that focuses on the semantic density of the series of six open-source online revision sessions. The outcome of the analysis is plotted in a graphical representation that visually describes the cumulative knowledge building during each lesson. The semantic profiles for each video of the online lessons illustrates the transformation of cumulative knowledge building that has been achieved. The analysis of the online lessons using semantic density have further indicated that the complexity of lessons does not necessarily decrease or limit the understanding of the pedagogy, in this case, financial mathematics. The examples in the online videos moved from simple to complex and demonstrated a link from one example to the next example.
A research report submitted in fulfillment of the requirements for the Master of Education, In the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Grade 12 Financial Mathematics; Legitimation Code Theory; online teaching material; SDG-4: Quality education; SDG-9: Industry, innovation and infrastructure